2002
DOI: 10.2175/193864702784162741
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Shear Solids Processing on Production of Volatile Sulfur Compounds From Anaerobically Digested Biosolids

Abstract: The emission of volatile sulfur compounds (VSCs) was evaluated for stored anaerobically digested biosolids cakes. This evaluation was conducted on the headspace of anaerobically stored cakes obtained from two municipal wastewater treatment plants. The objective of this investigation was to determine the impact of high-shear solids processing on VSC production from digested biosolids. Experiments were conducted on biosolids obtained from full-scale lowand high-solids centrifuges, and from screw conveyors. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The reactivation of pathogenic indicators in the digested sludge resulted from the change in physicochemical property of effluent sludge, such as the removal of VFAs, and NH 4 + ‐N, release of extra nutrients and shearing force change during the dewatering process (Murthy et al . ; Qi et al . ; Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…The reactivation of pathogenic indicators in the digested sludge resulted from the change in physicochemical property of effluent sludge, such as the removal of VFAs, and NH 4 + ‐N, release of extra nutrients and shearing force change during the dewatering process (Murthy et al . ; Qi et al . ; Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…The alldigested pellets were less persistent with added moisture, but more persistent with soil amendment. Recently, Murthy et al (2002) showed that odor compound production from digested biosolids peak after several days (approximately 1 week) of storage. The storage time used in these experiments was limited to 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have shown that the centrifugal dewatering process increases odor emissions from biosolids (Murthy et al, 2002;Murthy et al, 2003;Higgins et al, 2003). These studies have implicated shearing forces during centrifugation.…”
Section: Effect Of Solids Concentration On Methane Productionmentioning
confidence: 99%